2021
DOI: 10.1007/s10661-021-09212-w
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater aquatic reptiles (Testudines and Crocodylia) as biomonitor models in assessing environmental contamination by inorganic elements and the main analytical techniques used: a review

Abstract: chosen for each group (37%), we observed an increase in the use of non-destructive matrices in both groups (scale, blood, tail muscle, carapace). The majority of analysed studies used HNO 3 for the sample decomposition, with the majority of analyses being performed using atomic absorption spectroscopy (53%). Mainly blank controls (19%), analyte recovery (18%) and replicates (18%) were used as methods of validating analytical procedures. Furthermore, the studies used certified reference materials, which measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…Total mercury concentrations in both blood and dermis were significantly correlated with THg concentrations in other tissues, except for residual yolk. There is an impetus for non-lethal mercury sampling [42,62,66,67], and blood has proven a reliable indicator, showing high levels of correlation with internal organs (blood–muscle: R 2 = 0.9499 [59]; blood–muscle: R 2 = 0.82, blood–liver: R 2 = 0.79 [66]). We did not observe such high correlation coefficients, suggesting that although blood could potentially be used as a non-lethal indicator of mercury in hatchlings, this relationship appears stronger in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total mercury concentrations in both blood and dermis were significantly correlated with THg concentrations in other tissues, except for residual yolk. There is an impetus for non-lethal mercury sampling [42,62,66,67], and blood has proven a reliable indicator, showing high levels of correlation with internal organs (blood–muscle: R 2 = 0.9499 [59]; blood–muscle: R 2 = 0.82, blood–liver: R 2 = 0.79 [66]). We did not observe such high correlation coefficients, suggesting that although blood could potentially be used as a non-lethal indicator of mercury in hatchlings, this relationship appears stronger in adults.…”
Section: Discussionmentioning
confidence: 99%
“…THg concentrations in liver ranked comparatively low among all tissues, contradictory to high liver THg concentrations reported in adults [54,55,[59][60][61]. The liver is generally considered the main site of mercury storage and depuration [47,54,55,59,60,62], presenting two possibilities. First, liver THg concentrations observed in this study reflect differences in exposure route, with maternally deposited mercury being found in different tissues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The bioaccumulation of toxic metals by reptiles results from surface contact with the water and food chain [47,63,64], and the concentrations depend on the environmental levels of trace metals in the habitat, since they are absorbed and stored in the tissues [65]. Researchers have shown that the mercury concentrations in the muscles of freshwater animals varies widely depending on the capture location [59,66].…”
Section: Thg Bioaccumulationmentioning
confidence: 99%
“…The broad‐snouted caiman ( Caiman latirostris ) is widely distributed in South America, from the Northeast and across the Southeast and South of Brasil to Uruguay, northeast Argentina, southern Paraguay, and southwest to Bolivia (Verdade & Piña, 2007). Caiman latirostris has been used as a bioindicator of environmental contamination using chemical (Dos Santos, de Sousa Correia, & dos Santos, 2021), biochemical (Burella et al, 2018), genotoxic (López González et al, 2013; Poletta et al, 2011), histological (Stoker et al, 2008), and endocrine (Stoker et al, 2003) blood parameters. Blood samples offer a highly valuable approach for assessing the accumulation and biological consequences of contaminants in vertebrates, while avoiding destructive procedures (Fossi et al, 1998; Grillitsch & Schiesari, 2010).…”
Section: Introductionmentioning
confidence: 99%